A colocação dos pronomes clíticos no português falado em Luanda-Angola: um estudo sociolinguístico e sócio-histórico - Silva, Manoel Crispiniano Alves da (2022)
The placement of clitic pronouns is a morphosyntactic phenomenon that individualizes the Brazilian variety in relation to the European one. This is because, in European Portuguese, the pronominal placement is conditioned by linguistic factors – such as the element that precedes the verb and the syntactic context – while, in Brazilian Portuguese, there is a generalization of proclisis. This phenomenon has already been widely studied in the Brazilian sociolinguistic reality with diachronic and synchronic data from different theoretical perspectives. In African varieties of Portuguese, however, although there are already some studies about the variable phenomenon in question, developed based on indicative samples of the spoken Portuguese language, it is undeniable that there is still a lack of studies that analyze the variable linguistic patterns of the position of pronominal clitics. Thus, this research, based on the theoretical-methodological framework of the Theory of Language Variation and Change, aims to contribute to overcoming this gap, primarily seeking to analyze the patterns of placement of clitic pronouns in urban spoken Portuguese in Luanda, capital of Angola, considering the contexts formed by simple verbal lexical units with verbs in finite and infinite forms. For this, oral data collected in sociolinguistic interviews recorded in Luanda, in 2008 and 2013, with Angolans who declared having Portuguese as their mother tongue, belonging to the linguistic collection of the research project “In search of the roots of Brazilian Portuguese - Phase III”, located at the Portuguese Language Studies Center. Thus, the results show that the order of clitics in Luanda Portuguese is a variable phenomenon, with a higher frequency of use of the proclitic variant. The variability in the position of the clitics in this speech community is conditioned by linguistic and sociocultural factors, being selected as statistically relevant the favorability of proclisis in the following variables (i) Type of clause, (ii) Element that precedes the verb , (iii) Verb mood and form, (iv) Clitic type, (v) Education and (vi) Intercommunication Language. In summary, the results show that, in the sample of Portuguese from Luanda, proclisis is produced in all syntactic contexts, including in the face of traditional non-proclysing elements, such as subject and coordinating conjunction and when the verb is in the absolute initial position, non-variable context in the European standard. The comparative analysis between the varieties of Portuguese regarding the ordering of the pronominal clitics shows that, in a continuum, the Angolan Portuguese is the African variety that is closest to the Brazilian Portuguese, since it is possible to verify a tendency towards the generalization of proclisis in all contexts. Therefore, this investigation contributes to the agenda of studies that investigate the sociolinguistic reality of the varieties of Portuguese in Africa.